Energy Input on Cover Crop Cultivation (Agricultural Engineering, 2017)
The research was carried out in 2015-2016 at the Research Station Brody belonging to Poznan University of Life Sciences. The experiment was assumed with blocks randomized in four replications. The aim of the study was to determine the size and structure of energy inputs incurred on cover crops cultivation in different soil tillage systems. The cumulative energy consumption methodology was used to analyse the energy expenditure on field pea and white mustard seed. Based on the research, it was found that sowing field pea as a cover crop as compared to white mustard increased the cumulative energy input by 63.2%. Applied sowing technologies, regardless of cover crop species, reduced cumulative energy use by 22.5% (strip tillage) and direct sowing by 40.7% as compared to traditional tillage. The structure of energy input depended on the type of used cover crop species, which was based on the energy value of the seed used. The value of the energy efficiency index for growing both cover crop species increased with the simplification of the tillage.